2020
DOI: 10.3389/fmicb.2020.00242
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Zika Virus Endocytic Pathways in Human Glioblastoma Cells

Abstract: Zika virus (ZIKV) infections can cause microcephaly and neurological disorders. However, the early infection events of ZIKV in neural cells remain to be characterized. Here, by using a combination of pharmacological and molecular approaches and the human glioblastoma cell T98G as a model, we first observed that ZIKV infection was inhibited by chloroquine and NH 4 Cl, indicating a requirement of low intracellular pH. We further showed that dynamin is required as the ZIKV entry was affected by the specific inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 83 publications
2
33
0
Order By: Relevance
“…In particular, our early findings in the case of DENV serotype 2 suggest 5a as an inhibitor of autophagy and micropinocytosis mechanisms, which are relevant to DENV and other flaviviruses [ 26 , 27 ]. This inhibitory effect would likely affect the replication of other flaviviruses , which enter host cells via multiple pathways, including micropinocytosis, as has been demonstrated for ZIKV infections in glioblastoma cells [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, our early findings in the case of DENV serotype 2 suggest 5a as an inhibitor of autophagy and micropinocytosis mechanisms, which are relevant to DENV and other flaviviruses [ 26 , 27 ]. This inhibitory effect would likely affect the replication of other flaviviruses , which enter host cells via multiple pathways, including micropinocytosis, as has been demonstrated for ZIKV infections in glioblastoma cells [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selected compounds were first evaluated at a fixed 10 μM concentration for their potential inhibition of ZIKV-induced cytopathic effect in a MTS based TCID 50 assay [ 37 ], using cell lines which are physiologically relevant for ZIKV infection, including HUH7 hepatoma cells [ 38 ], dbtrg cells [ 28 ], and A549 cells, which support Zika virus infection in vitro [ 39 ]. The cell lines used were chosen to reflect the pathogenesis of ZIKV in liver (HUH7) and CNS tissues (dbtrg), in addition to a cell line where the ZIKV strain originally isolated in Uganda in 1947 grows and forms plaques particularly well (A549).…”
Section: Resultsmentioning
confidence: 99%
“… Li et al (2020) showed that chlorpromazine in the non-toxic concentrations in T98G cells inhibits ZIKV cell infection in a dose-dependent manner without influencing JEV copies of viral RNA ( Li et al, 2020 ).…”
Section: The Antiviral Activity Of Chlorpromazine Fluphenazine Perpmentioning
confidence: 99%
“…Moreover, transfection of cells with small interfering RNAs specific to clathrin heavy chain can also inhibit viral gene expression, indicating the essential role of clathrin in viral entry (PuZhang, 2008). Similarly, entry of Zika virus has also been shown to be significantly inhibited by CPZ (Li et al, 2020). CPZ slows or suppresses the replication of alphaviruses, hepatitis C virus, SARS-CoV-1, and MHV-2.…”
Section: Chlorpromazine and Viral Infectionsmentioning
confidence: 99%